2020
DOI: 10.1038/s41598-020-64285-w
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Algorithm using Multi-parametric MRI to Differentiate Benign from Malignant Myometrial Tumors: Machine-Learning Method

Abstract: This study aimed to develop a diagnostic algorithm for preoperative differentiating uterine sarcoma from leiomyoma through a supervised machine-learning method using multi-parametric MRI. A total of 65 participants with 105 myometrial tumors were included: 84 benign and 21 malignant lesions (belonged to 51 and 14 patients, respectively; based on their postoperative tissue diagnosis). Multi-parametric MRI including T1-, T2-, and diffusion-weighted (DW) sequences with ADC-map, contrast-enhanced images, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Malek [16] A simple algorithm showed 96.2% accuracy, 100% sensitivity and 95% specificity. The complex algorithm yielded accuracy, sensitivity and specificity of 100%.…”
Section: Authors Significant Results For Lesion Characterization: Dif...mentioning
confidence: 99%
See 2 more Smart Citations
“…Malek [16] A simple algorithm showed 96.2% accuracy, 100% sensitivity and 95% specificity. The complex algorithm yielded accuracy, sensitivity and specificity of 100%.…”
Section: Authors Significant Results For Lesion Characterization: Dif...mentioning
confidence: 99%
“…Ten studies were duplicates across PubMed and Scopus and thus eliminated, resulting in 744 studies to be screened. According to the previously described inclusion and exclusion criteria, 722 papers were excluded, and 6 full-text articles were included in this systematic review [16][17][18][19][20][21]. Details about the literature search results are reported in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…TCR combined with apparent diffusion coefficient (ADC) can completely differentiate sarcomas from uterine fibroids. Several studies [ 54 , 55 , 56 , 57 ] have found that diffusion-weighted imaging (DWI) high signal and low ADC values were predictors of uterine sarcoma, whereas slightly different ADC values were determined by other studies. DWI and ADC combined with lymph node enlargement or retroperitoneal masses [ 58 ] can improve the detection of uterine sarcomas.…”
Section: Imaging Examinationsmentioning
confidence: 99%
“…For uterine tumors with high T2 signal, radiomics combined with clinical variable models [ 76 , 77 ] can achieve predictive performance higher than that of imaging physicians. Malek et al [ 57 ] obtained the best simple decision tree with 96.2% accuracy, 100% sensitivity, and 95% specificity by analyzing 13 features of multiparametric MRI with a machine-learning algorithm, whereas the accuacy, sensitivity, and specificity of the complex tree were up to 100%. Good progress has also been made in radiomics based on ADC maps to differentiate uterine sarcomas from uterine leiomyomas [ 78 , 79 ].…”
Section: Imaging Examinationsmentioning
confidence: 99%